Addition of Carrot Juice (Daucus carota) to the Shelf Life and Organoleptic of Turkey Meatballs - Tasya Rahma Deni Situmorang; Achmad Sadeli; Usman Budi (Jurnal Peternakan Integratif, 2024)
Turkey is a type of poultry with characteristics and tastes similar to chicken meat, so turkey has the potential to be a raw material for meatballs. Carrots are also a source of natural antioxidants, the use of carrots so far has only been for vegetables and juice. Utilization in a fresh state has limitations because fresh carrots are prone to deterioration in quality. This study aims to determine the effect of adding carrot juice on the shelf life and organoleptic of turkey meatballs. This research was conducted in April 2024 at the Production Laboratory, Animal Husbandry Study Program, Faculty of Agriculture, Universitas Sumatera Utara. The design used in this study was RAL (Completely Randomized Design) with 4 treatments, namely P0 = 0 ml, P1 = 50 ml, P2 = 100 ml, P3 = 150 ml and 5 replications. The parameters used were shelf life and organoleptic color, taste, texture and aroma. The results of this study indicate that the addition of carrot juice can extend the shelf life of turkey meatballs. The best shelf life is in P3 with the addition of 150 ml of carrot juice with a shelf life of 5 days and the lowest shelf life is 1 day